Nanopore unstacking of single-stranded DNA helices - Chen, Peng (2012)
Time to unwind: The force-induced unstacking of individual single-stranded homopolymeric DNA helices is demonstrated during their translocation through an -hemolysin protein nanopore by electrophoresis (see picture). The unstacking energy and sequence-specific cooperativity are inferred from an analysis of the translocation kinetics.